استخلاص السيليلوز من المخلفات النباتية الجريد ومخلفات شجيرات البطاطا لتحظير خلات السيليلوز - العايش, ايمان; جابو, نور الهدى (جامعة الوادي University of Eloued, 2019)
تهدف هذه الدراسة الى تثمين مخلفات النخيل ونبات البطاطا ولإيجاد بدائل محلية للمواد الاولية وذلك بإعادة تدوير واستعمال مكوناتها كثروة متجدد، في هذا العمل استخدمنا هذه المخلفات كمصدر لا نتاج السليلوز، فتم استخلاصه عن طريق المعالجة الكيميائية ذلك بنزع كل المواد غير السليلوزية (non-cellulosique) فكان مردود النخيل (39.1%) أما البطاطا (48.6%) ثم تم تشخيصه بطيف الأشعة تحت الحمراء (FT-IR) خلال أهم مراحل المعالجة من اجل تتبع نقاوته بتتبع الوظائف الكيميائية المختلفة التي وضحت غياب وظائف المواد غير السليلوزية، طيف الاشعة الصينية (XRD) من أجل تحديد نسبة السليلوز المتبلور التي كانت (84.6%)، المجهر الالكتروني الماسح (SEM) من اجل مراقبة الخصائص البنيوية (المورفولوجية) للعينات، تقنية التحليل الكيميائي الطيفي (EDS) لتحديد العناصر الكيميائية، ولقد اشارت كل هذه الفحوصات إلى أن المعالجة الكيميائية المستخدمة كانت فعالة في إزالة المركبات غير السليلوزية السعف بينما كانت جزئية في عينة ساق البطاطا، كما تم تصنيع خل"This study aims to assess the waste from date palms and potatoes and to find local substitutes for raw materials by recycling and using their components as a renewable resource, the main one on the main component which is cellulose so we have exploited and pulled it through several methods. In this work, we used this waste as a source of cellulose production: they were extracted by chemical treatment by eliminating all non-cellulosic materials and gave a palm yield of 39.1%. Also The potato (48.6%) was diagnosed with Infrared Spectrum (FIT-IR). During the most important steps of the treatment to determine its purity by tracing the different chemical functions explaining the absence of the functions of non-cellulosic materials. XRD Chinese radiation spectrum to determine the percentage and purity of crystallized cellulose was (% 84.6). -Scan scanning electron microscopy for monitoring the morphological characteristics of samples. Chemical Analysis Method EDS for Detecting Chemical Elements. All of these tests showed that the chemical treatment used was effective in finding non-cellulosic palm leaf compounds while it is partial in the potato stem sample and also cellulose acetate was also made in from cellulose extracted from palm trees and confirmed by the infrared spectrum (FIT-IR) "ات السيليلوز انطلاقا من السليلوز المستخلص من النخيل وتم التأكد منه عن طريق طيف الأشعة تحت الحمراء (FT-IR).
مذكرة ماستر كيمياء
Keywords: السليلوز، النخيل، نبات البطاطا.; cellulose, palm tree, potato palnt.